Myths & legends an illustrated guide to their origins and meanings - Wilkinson, Philip (London Dorling Kindersley Limited, 2019)
What did Japanese mythology say about the beginning of the Universe? How did Oedipus become the classic tragic hero in Greek mythology? Who brought about the origin of death in Maori mythology? Combining vivid retellings of famous legends with over 1,000 illustrations of characters, famous artworks, and artefacts, Myths and Legends makes it easier than ever before to understand the stories that are central to every culture.
Includes index.
Keywords: Mythology; Legends